Prevalence of hydatid cyst in human and animals in Sulaimaniya city and Saedsadq distract - Mohamad O. Mohamad; Lazem H. Al-taie; Hersh A. Amin (مجلة كلية الطب, 2008)
Background: Hydatid disease is widespread and considered endemic in the Middle East and the Mediterranean, Iraq is one of the countries with a high endemicity of this disease. Objectives: The aim of this study is to diagnose hydatidosis and to identify the prevalence in human and animals in two different areas Sulaimaniya governorate which include Sulaimaniya city and Saedsadq district., Methods: Seroepidemiological survey was conducted by using enzyme-linked immunosorbent assay (ELISA) and Indirect Haemagglutination IHA to detect anti Echinococcus granulosus antibody in random blood samples (536) of different sex, ages, and occupation out patients, in Sulaimaniya and Saedsadq. In the animal study inspection and examination of the internal organs (liver, lungs, spleen and heart)